Social and Ecological Elements for a Perspective Approach to Citizen Science on the Beach - Fanini, Lucia; Costa, Leonardo Lopes; Zalmon, Ilana Rosental; Riechers, Maraja (Frontiers in Ecology and Evolution, 2021)
Sandy beaches are ecotonal environments connecting land and sea, hosting exclusive resident organisms and key life stages of (often charismatic) fauna. Humans also visit sandy beaches where tourism in particular moves billions of people every year. Though, instead of representing a connection to nature, the attitude towards visiting the beach is biased concerning its recreational use. Such “sun, sea and sand” target and its display seem to be deeply rooted in social systems. How could scientists engage the newest generations and facilitate an exit from this loop, fostering care (including participative beach science) and ultimately a sustainable sandy beach use? To tackle this question we applied the concept of social-ecological systems to the Littoral Active Zone (LAZ). The LAZ is a unit sustaining beach functionalities, though includes relevant features making a beach attractive to the public. Out of the analysis of the system LAZ in its social and ecological templates, we extracted elements suitable to the planning of citizen science programs. The leverage points perspective was integrated to needs identified in the analysis, through reconnecting-restructuring-rethinking the components of the system. Two cross-cutting approaches were remarked as important to social and ecological designs and break through the dominant perception of beaches as mere piles of sand: the physical dimension (LAZ) of the beach as a unit, and the use of communication through social media, suitable to both monitoring and scientific data collection, and to data communication and hedonistic display of a day on the beach.